PERLINDUNGAN HUKUM BAGI ANAK KORBAN EKSPLOITASI SEKSUAL - Rizki, Ridwan; DM, M. Yusuf; Andrizal (Collegium Studiosum Journal, 2025)
The phenomenon of child sexual exploitation shows an alarming trend. Although the number of cases is not always high quantitatively, the impact on victims is extremely serious and multidimensional affecting physical, psychological, social aspects, and the child’s future. Reported cases often involve girls under the age of 18 who fall victim to people close to them, such as familiar adults, neighbors, or even family members. In several instances, victims are drawn into covert prostitution networks, either directly or through social media, where they are lured with promises of money, jobs, or even love, only to end up being trafficked and sexually exploited. The aim of this research is to analyze Legal Protection for Children Victims of Sexual Exploitation in the Jurisdiction of Siak Police, to examine the obstacles in providing such protection, and to explore solutions to overcome these challenges. This study uses a sociological legal research method. Based on the findings, it is revealed that while legal protection for children victims of sexual exploitation in the jurisdiction of Siak Police is already in place, its implementation is not yet optimal, due to various challenges both in law enforcement and victim support services. This is evident from the continued occurrence of child sexual exploitation cases, both those that have been handled and those that remain undisclosed. This situation shows that, although legal instruments and related institutions exist, their implementation at the practical level is not yet fully effective in providing maximum protection to children as the most vulnerable group. One key indicator of the inadequacy of legal protection is the recurring cases of child sexual exploitation. These cases occur not only in private environments such as homes or schools but also in public spaces, which should be safe for children.